Parental leave policies and socio-economic gaps in child development: Evidence from a substantial benefit reform using administrative data - Mathias Huebener; Daniel Kuehnle; C. Katharina Spiess (Labour Economics, 2019)
This paper examines the effects of substantial changes in paid parental leave on child development and socio-economic development gaps. We analyse a German reform that replaced a means-tested with an earnings-related benefit scheme. Higher-income households benefited relatively more from the reform than low-income households. The reform expanded paid leave in the first year, while it removed paid leave in the second year after childbirth. We compare children born around the eligibility cut-off on January 1st 2007 and contrast them with children from the preceding, unaffected cohort within a difference-in-differences approach. The analysis is based on administrative data from mandatory school entrance examinations containing detailed child development assessments at age six. Our precise and robust estimates reveal no effects of the changes in parental leave benefits on child development across various socio-economic groups, and consequently no effects on socio-economic development gaps. However, based on administrative employment data, we document substantial effects on maternal employment and family income. The paper concludes that reform effects on today's mothers are not sacrificed by increases in SES gaps of the future workforce.
Keywords: J13; J18; J22; J24; 330; Parental leave benefits; Child development; School readiness; Motor skills; Language skills; Socio-emotional stability; Elterngeld